Investigation into the Challenges Experienced by School Management Teams (SMTs) Post-Pandemic in Rural High Schools in the Mopani-West Education District - Sibuyi, Nyiko Amos; Segooa, Mapule Yvonne; Molise, Habasisa Vincent; Solomon Modiba, Ngwako; Mafumo, Thinavhudzulo (Research in Social Sciences and Technology- OpenED Network, 2024)
The purpose of this study was to investigate the challenges faced by SMTs in dealing with poor academic performance in the Mopani-West District of Limpopo Province, South Africa. Studies have indicated that schools in rural areas fail to meet their full potential due to a combination of factors including insufficient instructional resources, shortage of qualified educators, insufficient infrastructure, and poverty and inequality. The study adopted a qualitative approach following an interpretative case study design. Using purposive sampling a total of 18 participants, comprising six principals, six departmental heads, and six learners who met the research criteria were selected. The study sample included one principal, one departmental head, and one learner from each of these six schools in the Mopani-West District. Three schools from the sample were identified as high-performing, while the other three were identified as underperforming. Data were elicited using semi-structured interviews, followed by thematic data analysis to unveil rich narratives and patterns within the research inquiries. The findings of the study revealed that resource scarcity in schools significantly hampered the quality of education. Issues such as insufficient teaching materials, a shortage of teachers, and the absence of technology create stark disparities between less and more privileged schools. The study also highlighted the impact of inadequate infrastructure on learning as one of the pressing concerns that compromise quality teaching and learning. Recommendations were made accordingly.